Peculiarities of development and metabolism of Streptococcus thermophilus strains under different conditions of deep liquid phase cultivation - G. M. Sviridenko; O. M. Shukhalova; E. S. Danilova (Пищевые системы)
The microflora of most fermented dairy products, including cheeses, consists entirely of lactic acid bacteria, i. e., bacterial starter cultures with different species and strain composition that are specially introduced into the mixture. The species composition of the starter must ensure the intensity and direction of the microbiological and biochemical processes of the produced product and guarantee its safety, quality and storability. In particular, lactic acid bacteria transform the main components of milk (protein, milk fat, lactose) into taste, aromatic, and biologically active substances involved in the formation of identification and organoleptic characteristics of fermented dairy products. The number of starter microorganisms in fermented dairy products, including cheeses, significantly exceeds the content of any foreign microflora and can cause the appearance of organoleptic defects such as acid, bitterness, non-specific off-taste or excessive gas formation. The ability of microorganisms to form certain metabolic products is determined both by their species and strain properties, and by cultivation conditions. These include, first of all, the composition of the development environment and temperature conditions of cultivation. By combining the composition of the starter and selecting favorable modes for cultivating microorganisms, it is possible to achieve optimal development of the starter microflora, obtaining products with the desired quality characteristics. This article presents the results of a comparative assessment of the properties of production strains of Streptococcus thermophilus during their development in dairy environments at optimal temperatures (41 ± 1) °C, simulating conditions for the production of fermented milk products, as well as in modes simulating cheese ripening conditions (11 ± 1) °C and 4% table salt concentration. The nature of the enzymatic processes of glycolysis, proteolysis, lipolysis, and flavor formation as a result of the metabolism of these cultures was also assessed.